1840. Development of an Innovative Antibiotic Prescribing Dashboard to Enhance Antimicrobial Stewardship in the Ambulatory Care Setting. (26th November 2018) - Gentry, Erin; Davis, Sarah; Collins, Cliff; Dubey, Mansi; Sweeney, Chloe; Spencer, Melanie; Handy, Elizabeth; Davidson, Lisa
Abstract: Background: The Carolinas HealthCare Outpatient Antimicrobial Stewardship Empowerment Network (CHOSEN) collaborates with more than 150 primary care ambulatory practices to improve antibiotic use in the Charlotte, NC area. CHOSEN aims for a 20% reduction in outpatient antimicrobial prescribing over 2 years with a focus on acute respiratory conditions. Initial qualitative research of provider interviews with 17 providers at 13 practices revealed the need for improved clinician reporting of prescribing rates and trends. Methods: Working with our research and analytics division, a strategy team including clinicians, quality and pharmacy identified key drivers of over prescribing and target conditions. Previous antibiotic prescribing data collected from 281, 315 adult and pediatric patients seen by nearly 900 providers was analyzed and served as a baseline. ICD-9 and 10 codes associated with acute sinusitis, nonsuppurative otitis media, acute bronchitis, cough, non-bacterial pharyngitis, upper respiratory infection, common cold, allergic rhinitis and influenza were included. Prescribing data were abstracted at the encounter level. Prescribing rates were calculated for pediatrics, internal medicine, family medicine and urgent care practices to target a 10% reduction in 2018 compared with 2017. Results: A dashboard was developed in Microsoft Power BI with means to view prescribing data by indication and antibiotics, comparing year-to-year and rolling 24-months. Dashboard capabilities include option to drill down to the practice and provider level. An overall CHOSEN target rate for 2018 was set at 41.9% based on a baseline prescribing rate of 45.7%. Final target rates for specialties, pediatrics, internal medicine, family medicine and urgent care, were 40.8%, 38.7%, 40% and 47.2%, respectively. Provider and practice leaders were educated on use of the dashboard, along with tips to address high prescribing. Data are updated monthly and highest prescribing groups are targeted for additional onsite education. Conclusion: The development of an innovative antibiotic prescribing dashboard is achievable. CHOSEN successfully designed and applied a dashboard with focus on reduction of inappropriate antibiotic prescribing in an ambulatory care setting. Disclosures: E. Gentry, Duke Endowment: Grant Investigator, Grant recipient. C. Sweeney, Duke Endowment: Grant Investigator, Grant recipient. M. Spencer, Duke Endowment: Grant Investigator, Grant recipient. Eli Lilly and Company: Grant Investigator, Grant recipient. E. Handy, Duke Endowment: Grant Investigator, Grant recipient. L. Davidson, Duke Endowment: Grant Investigator, Grant recipient.